Oxidative conditions prevail in severe IUGR with vascular disease and Doppler anomalies. (August 2015) - Maisonneuve, Emeline; Delvin, Edgard; Ouellet, Annie; Morin, Lucie; Dubé, Johanne; Boucoiran, Isabelle; Moutquin, Jean-Marie; Fouron, Jean-Claude; Klam, Stephanie; Levy, Emile; Leduc, Line
Abstract Objective: Intrauterine growth restriction (IUGR) and prenatal exposure to oxidative stress are thought to lead to increased risks of cardiovascular disease later in life. The objective of the present study was to document whether cord blood oxidative stress biomarkers vary with the severity of IUGR and of vascular disease in the twin pregnancy model in which both fetuses share the same maternal environment. Methods: This prospective cohort study involved dichorionic twin pairs, with one co-twin with IUGR. Oxidative stress biomarkers were measured in venous cord blood samples from each neonate of 32 twin pairs, and compared, according to severity of IUGR (IUGR <5th percentile), Doppler anomalies of the umbilical artery and early onset IUGR (in the second trimester) of the growth restricted twin. Results: Oxidized Low-Density Lipoproteins (oxLDL) and Malondialdehyde (MDA) concentrations were increased proportionally in cases of severe IUGR. OxLDL concentrations were also increased in cases of IUGR with Doppler anomaly. Conclusion: Our data indicate that severe IUGR, is related to a derangement in redox balance, illustrated by increased venous cord blood oxidative stress biomarkers concentrations. Severe IUGR and IUGR with abnormal Doppler can be translated into conditions with intense oxidative stress.